Understanding the Antecedents and Consequences of Residents’ Attitudes Toward Tourism Development and Environmental Responsibility in Community-Based Tourism Villages: A Sustainable Tourism Perspective - Sri Ismulyati; Hubertina Karolina Ngarbingan; Ike Janita; Ginta Ginting (AIBPM Publisher, 2026)
The development of sustainable tourism has become a central focus in the tourism sector. While its economic benefits are well recognized, tourism must also take responsibility for maintaining environmental sustainability. Despite its positive impacts, tourism can also bring negative effects on the environment. To support the development of environmentally responsible tourism strategies, this study proposes a model that integrates two theoretical approaches: Norm Activation Theory (NAT) and the Theory of Planned Behavior (TPB). Conceptually, this research aims to develop and test a model that provides a more comprehensive understanding of the factors shaping community attitudes toward responsible tourism development from the supply-side perspective. This study involved 165 respondents who are residents of three tourism villages in the Special Region of Yogyakarta (DIY): (1) Nglanggeran Tourism Village (Gunungkidul Regency), (2) Krebet Tourism Village (Bantul Regency), and (3) Kelor Tourism Village (Sleman Regency). The sampling technique used was non-random purposive sampling, and data were analyzed using SmartPLS to examine the relationships among variables. The results show that the intention of local communities in tourism villages to behave in an environmentally responsible way is strongly influenced by a combination of personal and social factors. Personal norms, which reflect individuals’ internal values, are found to be the strongest drivers in shaping positive attitudes toward environmental responsibility. These positive attitudes, in turn, become key predictors of the intention to act responsibly toward the environment. Social norms, or the expectations of the surrounding community, also play a role in encouraging pro-environmental attitudes, although their influence is weaker than that of personal norms. Moreover, perceived behavioral control is also important, as individuals’ confidence in their ability to carry out environmentally responsible actions significantly affects their intentions. The study further reveals a significant mediating effect, showing that personal and social norms indirectly influence behavioral intentions through attitudes. This finding highlights that attitude serves as a vital link that translates personal values and social influences into concrete intentions to act responsibly.